2012
DOI: 10.1152/ajpcell.00063.2011
|View full text |Cite
|
Sign up to set email alerts
|

Increased Na+/H+ exchanger activity on the apical surface of a cilium-deficient cortical collecting duct principal cell model of polycystic kidney disease

Abstract: Pathophysiological anomalies in autosomal dominant and recessive forms of polycystic kidney disease (PKD) may derive from impaired function/formation of the apical central monocilium of ductal epithelia such as that seen in the Oak Ridge polycystic kidney or orpk ( Ift88Tg737Rpw) mouse and its immortalized cell models for the renal collecting duct. According to a previous study, Na/H exchanger (NHE) activity may contribute to hyperabsorptive Na+movement in cili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
2
15
0
1
Order By: Relevance
“…NHE1 was localized in the intracellular compartment and at the membranes in both cell lines, but cilia (Ϫ) demonstrated increased localization to the apical membranes (green) (Fig. 2B, yellow arrow pointing apical NHE-1) compared with cilia (ϩ) cells, as previously reported (18). Other NHE isoforms were also determined, but there was no difference in localization for NHE-2, NHE-3, NHE-4, and ErbB2 between cilia (ϩ) and cilia (Ϫ) cells by immunofluorescence.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…NHE1 was localized in the intracellular compartment and at the membranes in both cell lines, but cilia (Ϫ) demonstrated increased localization to the apical membranes (green) (Fig. 2B, yellow arrow pointing apical NHE-1) compared with cilia (ϩ) cells, as previously reported (18). Other NHE isoforms were also determined, but there was no difference in localization for NHE-2, NHE-3, NHE-4, and ErbB2 between cilia (ϩ) and cilia (Ϫ) cells by immunofluorescence.…”
Section: Resultssupporting
confidence: 85%
“…The role of NHE in PKD has not been well studied. However, a recent study using orpk collecting duct cells demonstrated that NHE function is activated in the apical surface of these cilia (Ϫ) cells but not in control cells determined by intracellular pH measurement utilizing fluorescence imaging (18). In addition, urine from kidney-specific cilia knockout mice was acidic compared with wild-type mice, which supports increased apical activity of NHE in this ARPKD mouse model.…”
Section: Discussionmentioning
confidence: 75%
“…Toutefois, in vivo, les résultats sont plus ambigus, puisque certaines des souris mutantes pour ces gènes n'expriment aucun phénotype rénal. Chez la souris Inv -/-(Nphp2 -/-), la présence de kystes rénaux n'est d'ailleurs associée à aucune alté-ration de la structure, de la longueur ou du mécanisme de flexion des cils primaires du rein, contrairement à l'effet de cette même mutation sur les cils nodaux [11,12] [21]. Le glomérule peut également s'élargir et former des kystes glomérulaires.…”
Section: Nphp1-9unclassified
“…The phenotype arose from an insertional mutation in the Ift88 gene encoding the protein IFT88 (Polaris), a mutation that leads to the lack of a well-formed central cilium in multiple tissues. The study by Olteanu et al (8) in this issue, a collaboration between a number of labs with complementary strengths in renal and epithelial physiology, utilizes both conditionally immortalized cortical collecting duct (CCD) principal cells (PCs) isolated from the ORPK mouse, as well as a kidney-specific conditional cilium knockout mouse generated from the ORPK mouse to assess altered renal transporter activity and polarity in these cilia-deficient cells. A previous study from this group in cilium-deficient CCD PCs reported a fourfold increase in apical epithelial Na ϩ channel (ENaC)-mediated sodium reabsorption (9), suggesting that the ciliumsensing pathway controls ENaC activity, a potential clinically relevant finding given the early onset of hypertension that is observed in the ARPKD population (3).…”
mentioning
confidence: 99%
“…The studies of Olteanu et al (8,9) are relevant to the growing body of literature on the relationships between ciliary structure/function and renal epithelial transport, and may be relevant to hypertension via control of ENaC abundance. However, careful evaluation is needed before concluding that the authors' meticulous studies in the ORPK model are applicable to human PKD.…”
mentioning
confidence: 99%